Pengaruh Sirkel Pertemanan dan Kepercayaan Diri Terhadap Konformitas Sosial : Studi Kuantitatif pada Mahasiswa Semester 2 Program Studi Kebidanan di Politeknik Kebidanan Semarang - Safitri, Dwi; Margaretha Maria Shinta Pratiwi; Hardani Widiastuti (Universitas Darul Ulum, 2025)
This study aims to examine the influence of friendship circles and self-confidence on social conformity among early semester midwifery students at Poltekes Semarang. A total of 70 second-semester students participated as respondents in this quantitative study. Data were collected using validated and reliable questionnaires measuring friendship circles, self-confidence, and social conformity. Descriptive statistics showed that students had moderately high scores on friendship circles and self-confidence, and a moderate tendency toward social conformity. Correlation analysis revealed a significant positive relationship between friendship circles and social conformity (r = 0.62, p < 0.01), and a significant negative relationship between self-confidence and social conformity (r = -0.45, p < 0.01). Multiple linear regression analysis indicated that both friendship circles and self-confidence significantly predicted social conformity (R² = 0.52, p < 0.001). The findings suggest that strong peer connections increase conformity tendencies, while higher self-confidence reduces it. These results highlight the importance of balancing peer influence and self-confidence development in midwifery students to foster healthy social adaptation without loss of individuality.